2015
DOI: 10.1162/pres_a_00212
|View full text |Cite
|
Sign up to set email alerts
|

Sending an Avatar to Do a Human's Job: Compliance with Authority Persists Despite the Uncanny Valley

Abstract: Just as physical appearance affects social influence in human communication, it may also affect the processing of advice conveyed through avatars, computer-animated characters, and other human-like interfaces. Although the most persuasive computer interfaces are often the most human-like, they have been predicted to incur the greatest risk of falling into the uncanny valley, the loss of empathy attributed to characters that appear eerily human. Previous studies compared interfaces on the left side of the uncan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 134 publications
(162 reference statements)
0
12
1
Order By: Relevance
“…We would expect inconsistent realism and eeriness to have the opposite effect. Nevertheless, Patel & MacDorman (2015) found that although an animated character was more eerie, less attractive, and less human than its real counterpart, it did not reduce the intention to comply with advice. Based on the assumption that flaws in realism cause negative affective evaluations, namely, eeriness that decreases source credibility, we hypothesized that (H3) a high-realism source will be more persuasive than a low-realism source.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…We would expect inconsistent realism and eeriness to have the opposite effect. Nevertheless, Patel & MacDorman (2015) found that although an animated character was more eerie, less attractive, and less human than its real counterpart, it did not reduce the intention to comply with advice. Based on the assumption that flaws in realism cause negative affective evaluations, namely, eeriness that decreases source credibility, we hypothesized that (H3) a high-realism source will be more persuasive than a low-realism source.…”
Section: Introductionmentioning
confidence: 91%
“…The affective lip and eyebrow movements were precisely synchronized to the video by hand but appeared less emphatic. The same computer model had been used in a different scenario and found to be significantly more eerie than the real actor (Patel & MacDorman, 2015).…”
Section: Depictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most importantly, by delineating different aspects of discomfort scientists may ultimately be able to predict which aspect(s) compromise(s) people's willingness to engage with or accept robots (Ho & MacDorman, 2010;Patel & MacDorman, 2015).…”
Section: Discussionmentioning
confidence: 99%